2015
DOI: 10.1186/s12871-016-0230-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of sevoflurane preconditioning on ischemia-reperfusion injury in patients undergoing reconstructive plastic surgery with microsurgical flap, a randomized controlled trial

Abstract: BackgroundIn many clinical conditions that involve free flaps and tissue transplantations the possibility of minimizing ischemia-reperfusion injury can be a determinant factor for the success of the surgery itself. We hypothesize that preconditioning with sevoflurane is a protective factor against ischemia-reperfusion injury.MethodsIn this randomized controlled trial, patients ASA I-II undergoing breast reconstruction with deep inferior epigastric perforator flaps were allocated into two groups and analyzed: g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Sevoflurane exhibited favorable effects in animal experiments, but clinical evidence indicated no survival difference between diabetic and non-diabetic groups 11 . However, Sevoflurane preconditioning cardioprotection is undoubted in clinical applications [32][33][34] . Our study demonstrates that preconditioning can directly positively influence cell survival signaling (MAPK) in the diabetic condition, rescuing the energetic pathway independently of endogenously suppressed metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane exhibited favorable effects in animal experiments, but clinical evidence indicated no survival difference between diabetic and non-diabetic groups 11 . However, Sevoflurane preconditioning cardioprotection is undoubted in clinical applications [32][33][34] . Our study demonstrates that preconditioning can directly positively influence cell survival signaling (MAPK) in the diabetic condition, rescuing the energetic pathway independently of endogenously suppressed metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Volatile anesthetics attenuated IRI-related endothelial destruction in some animal studies [ 13 15 ]. However, clinical studies investigating the endothelial protective effect of volatile anesthetics show conflicting results [ 16 , 17 ]. In addition, few clinical studies revealed the different effect of volatile anesthetics and propofol in terms of endothelial protection against IRI during TKA.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant developments have been made in understanding the mechanisms of I/R injury and in developing strategies to make myocardial tissue more resistant to ischemia or to limit reperfusion injuries [4]. Among these cardioprotection strategies, APc with halogenated agents, of which SEV, has proven its effectiveness in both animals [40] and humans [41,42]. However, the way in which APc contributes to the reported myocardial protection remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%